Government Expenditure on Education, Educational Index, and Economic Growth in Nepal: An ARDL-ECM Approach - Duwal, Niroj; Suwal, Sunil (Heca Sentra Analitika, 2024)
Education is a key priority in economic development, significantly impacting growth and society through its role in enhancing human capital and advancing technological knowledge. Government spending on education is crucial for providing equitable access to quality education and is widely believed to stimulate economic growth. This study examines the relationship between education, government expenditure on education, and economic growth in Nepal from 1990 to 2022, using the Autoregressive Distributed Lag (ARDL) model and the Error Correction Model (ECM) to assess long-run and short-run impacts. The findings reveal that the educational index, gross capital formation, and population have a positive and significant impact on economic growth. In contrast, government expenditure on education, domestic credit to the private sector, and trade openness have negative and insignificant effects on long-run economic growth. Additionally, the educational index shows a negative and significant impact on economic growth in the short run. The study’s policy recommendations emphasize the need to increase government spending on education, implement effective mechanisms for spending, and enhance credit availability and trade openness to boost economic growth.